2013
DOI: 10.1123/tsp.27.2.120
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Survey of Interpersonal Conflict at Major Games and Championships

Abstract: Interpersonal conflict is a common factor reported by governing bodies and their athletes when preparing for, or competing in, major games and championships (Olusoga, Butt, Hays, & Maynard, 2009). The aim of this study was to conduct a preliminary exploration of a UK home nation’s athletes, management, and support staff experiences of interpersonal conflict during competition. Ninety participants who had represented or worked for their nation at major games or championships completed a detailed survey of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 20 publications
2
36
1
1
Order By: Relevance
“…Mellalieu et al (2013), investigating 588 conflict at major sport events, found that most responses to conflict were perceived negative 589 (65-70%; N = 90), whereas only few were perceived positive or neutral (5-29%). Negative 590 cognitive effects included worry, confusion, or even panic; positive cognitions related to 591 increased focus and task clarity.…”
Section: Intrapersonal Consequences Interpersonal Conflict Is Likelymentioning
confidence: 99%
See 4 more Smart Citations
“…Mellalieu et al (2013), investigating 588 conflict at major sport events, found that most responses to conflict were perceived negative 589 (65-70%; N = 90), whereas only few were perceived positive or neutral (5-29%). Negative 590 cognitive effects included worry, confusion, or even panic; positive cognitions related to 591 increased focus and task clarity.…”
Section: Intrapersonal Consequences Interpersonal Conflict Is Likelymentioning
confidence: 99%
“…They described conflict as short-lived and occurring only a 121 few times during major events, however, long-term conflict was also reported among 122 participants of all groups. Mellalieu et al's (2013) study offered a first insight into conflict in 123…”
Section: Developing a Definition Of Interpersonal Conflict Within Spomentioning
confidence: 99%
See 3 more Smart Citations